To determine the correct polynomial subtraction, we can perform the operation step-by-step for the expression:
\[ (2x^2 + 6x + 1) - (3x^2 + 3x + 9) \]
We can rewrite it as:
\[ 2x^2 + 6x + 1 - 3x^2 - 3x - 9 \]
Now, we will combine like terms:
-
For \(x^2\) terms: \[ 2x^2 - 3x^2 = -1x^2 = -x^2 \]
-
For \(x\) terms: \[ 6x - 3x = 3x \]
-
For constant terms: \[ 1 - 9 = -8 \]
Putting it all together, we get:
\[ -x^2 + 3x - 8 \]
Now, we will compare this result with the options provided:
- \((2x^2 + 6x + 1)−(3x^2 + 3x + 9) = -x^2 + 3x - 8\) (Correct)
- \((2x^2 + 6x + 1)−(3x^2 + 3x + 9) = -5x^2 + 3x - 8\) (Incorrect)
- \((2x^2 + 6x + 1)−(3x^2 + 3x + 9) = 5x^2 + 9x + 10\) (Incorrect)
- \((2x^2 + 6x + 1)−(3x^2 + 3x + 9) = x^2 + 3x + 8\) (Incorrect)
Therefore, the correct example that demonstrates polynomial subtraction is:
\((2x^2 + 6x + 1)−(3x^2 + 3x + 9) = -x^2 + 3x - 8\).